2009
DOI: 10.1007/s11814-009-0158-y
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study of the Dufour and Soret effects on unsteady natural convection flow past an isothermal vertical cylinder

Abstract: The Dufour and Soret effects on the unsteady laminar free convective flow with mass transfer flow past a semi-infinite isothermal vertical cylinder were studied numerically. The governing partial differential equations were converted into a non-dimensional form and solved numerically by applying a Crank-Nicolson type of implicit finitedifference method with a tri-diagonal matrix manipulation and an iterative procedure. For the hydrogen-air mixture, which is a non-chemical reacting fluid, the profiles of the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The system of nonlinear differential equations (18) subject to boundary conditions (19) evident that the temperature of the fluid increases whereas the concentration decreases with the increasing of Sr and Du. This is because of the difference between the temperatures of the fluid and surface as well as the difference between concentrations of the fluid and surface concentrations are increased with Sr and Du.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The system of nonlinear differential equations (18) subject to boundary conditions (19) evident that the temperature of the fluid increases whereas the concentration decreases with the increasing of Sr and Du. This is because of the difference between the temperatures of the fluid and surface as well as the difference between concentrations of the fluid and surface concentrations are increased with Sr and Du.…”
Section: Resultsmentioning
confidence: 99%
“…The system of (18) is solved numerically subject to boundary conditions (19) using the quasilinearization method given by Bellman and Kalaba [26]. Let ( , = 1, 2, .…”
Section: Solution Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…The Soret effect, though generally neglected due to its comparatively smaller magnitude than the effect described by Fick's law has been of research interest by many. [8][9][10][11][12] This is due to the prominent role it plays in processes like the separation of isotopes and gas mixtures having very light H He ( , ) 2 , and medium N air ( , ) 2 molecular weight. Seth et al [13][14][15] studied chemical reaction and radiation of a magnetohydrodynamics (MHD) flow on a vertical plate in motion when in rotation with Hall current applied and reported that chemical reaction reduces the momentum and species concentration.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the generation of mass flux by composition gradients with the influence of temperature gradients creates an effect called the Soret effect which is also known as thermal diffusion. The Soret effect, though generally neglected due to its comparatively smaller magnitude than the effect described by Fick's law has been of research interest by many 8–12 . This is due to the prominent role it plays in processes like the separation of isotopes and gas mixtures having very light false(H2,Hefalse) $({H}_{2},He)$, and medium false(N2,airfalse) $({N}_{2},air)$ molecular weight.…”
Section: Introductionmentioning
confidence: 99%